The Analysis of the Water Balance of the Soil in the North of Jordan during (1970 - 2009) - Mohammad Zeitoun (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The study aimed to identify water balance in the north of Jordan to see the periods of water surplus and water deficit. This study is beneficial for the agricultural sector through exploiting the periods of water surplus when the soil is saturated and does not suffer from a lack of moisture and when it can be useful in to depend on rain fed agriculture as a method of irrigation. It crucial to know the periods when there is water deficit to be cautious when there is a lack of moisture which may be harmful to crops consequently, avoiding this period or using other methods of irrigation to water the crops. Four climatic stations in the northern part of Jordan were included in the study, namely: (R'as Munif, Al-Baqura, Irbid and Mafraq) to provide measurements of temperature and rain for long periods of time. The amended Thornthwaite method of 1955 and rain data and annual temperature between the years (1970 – 2009) were used in the calculation of water balance. The water balance was calculated by using the amended Thornthwaite method to calculate the average of the potential evapotranspiration then to calculate water balance accordingly. The results indicated that there were two periods in terms of spatial distribution of moisture: water surplus which lasted for (3 – 5) months and water shortage which lasted for (7 – 9) months. R'as Munif station scored the highest water surplus which amounted to (418 mm) and the longest period of water deficient was scored in Mafraq which lasted for ninth months. The highest water deficient was scored in Al-Baqura station which reached to (1046mm).